GANT‐61 and GDC‐0449 induce apoptosis of prostate cancer stem cells through a GLI‐dependent mechanism. Issue 4 (5th January 2018) - Tong, Wangxia; Qiu, Lei; Qi, Meng; Liu, Jianbing; Hu, Kaihui; Lin, Wenxiong; Huang, Yan; Fu, Junsheng
Abstract: Aberrant reactivation of the Sonic Hedgehog (SHH) signaling pathway promotes prostate cancer (PC) growth and progression by regulating cancer‐related genes through its downstream effectors GLI1 and GLI2. Therefore, targeting the SHH‐GLI pathway provides an alternative approach to avoid cancer progression. The aim of this study was to delineate the underlying molecular mechanisms by which GDC‐0449 (a SMO receptor inhibitor) and GANT‐61 (a GLI transcription factor inhibitor) regulate cellular proliferation and self‐renewal in human PC stem cells (ProCSCs). Inhibition of the SHH signaling pathway by GANT‐61 induced apoptosis with more efficacy than by GDC‐0449 in ProCSCs and PC cell lines. GLI1 and GLI2 expression, promoter‐binding activity and GLI‐responsive luciferase reporter activity were all decreased with either GDC‐0449 or GANT‐61 treatment. Expression of Fas, DR4, DR5, and cleavage of caspase‐3 and PARP were increased, whereas levels of PDGFR‐α and Bcl‐2 were reduced. Double knockout of GLI1 and GLI2 using shRNA abolished the effects observed with either GDC‐0449 or GANT‐61 treatment. Collectively, our results showed that GANT‐61 and GDC‐0449 induced ProCSC apoptosis by directly or indirectly inhibiting the activities of the GLI family transcription factors, may enhance the efficacy of PC treatment. Abstract : We demonstrated that GDC‐0449 and GANT‐61 inhibited prostate cancer stem cell (ProCSC) proliferation by inducing apoptotic genes through the SHH signaling pathway. Moreover, we showed that GLI1/GLI2 played a significant role in this regulation, as double knockdown of GLI1/GLI2 in ProCSCs almost completely eliminated the anti‐proliferative/pro‐apoptotic effects by GANT‐61 and GDC‐0449. Although GDC‐0449 has been approved by the FDA and EMA for treating breast cancer patients and has shown promising preclinical tumor suppressing effects in multiple other cancers, much less information has been reported for GANT‐61 function in cancer. Also, this is the first study demonstrating the effect of these two drugs on ProCSCs. In our study, GANT‐61 exhibited greater efficacy than GDC‐0449 in inhibiting proliferation and inducing apoptosis, providing an alternative targeting approach that may be more effective in therapeutic treatment.